Subject‐specific hand grip fatigability indicator determined using parameter identification technique - Liu, Bin; Ma, Liang; Zhang, Wei; Zhang, Zhanwu (Human factors and ergonomics in manufacturing & service industries, 2019)
During hand grip operations, the fatigability of the local muscle determines the antifatigue capacity and influences the risk of injury of the workers. This study proposes a new hand grip subject‐specific fatigability indicator using a parameter identification technique from a physiologically based muscle fatigue model. Experimental measurements were conducted in a laboratorial fatiguing operation with a fixed external load (5 kg) under a static posture. Sixty participants (30 males and 30 females) participated in the experiment. Subject‐specific hand muscle fatigue rates (k) were identified by performing regressions of the muscle strength during time intervals using the muscle fatigue model. The majority (46/60) of the goodness of fit statistics (R2) was over 0.70, which indicates the validity of using the fatigue rate (k) as a hand grip fatigability indicator. Individual differences in the hand grip fatigue rate (k) were substantial, ranging from 0.14 to 2.57 min−1 with a coefficient of variation of 59.0%. The gender effect and body mass index did not exhibit significant influences on the hand grip muscle fatigue rates (k).